2015
DOI: 10.1002/pam.21857
|View full text |Cite
|
Sign up to set email alerts
|

Hold Your Fire: Did the 1996 Federal Gun Control Act Expansion Reduce Domestic Homicides?

Abstract: In 1996, Congress expanded the federal Gun Control Act (GCA) to prohibit defendants convicted of a qualifying domestic violence misdemeanor from possessing or purchasing a firearm. Using the FBI's Supplementary Homicide Reports along with homicide data collected from selected state law enforcement agencies, I investigate if this expansion was successful in reducing homicides among the target groups. I use variation from a legal loophole and a series of circuit court decisions to generate difference-indifferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 33 publications
(33 reference statements)
2
32
0
Order By: Relevance
“…Compared to other women in abusive relationships, women in abusive relationships where the abuser had access to a gun were at 25 times the risk of being killed in a femicide-suicide. At the household level, households with a gun and a history of domestic violence were at 20 times the risk of partner homicide compared to households with a history of domestic violence, but without the presence of a gun (Raissian, 2016).…”
Section: Firearms and Femicidementioning
confidence: 96%
See 2 more Smart Citations
“…Compared to other women in abusive relationships, women in abusive relationships where the abuser had access to a gun were at 25 times the risk of being killed in a femicide-suicide. At the household level, households with a gun and a history of domestic violence were at 20 times the risk of partner homicide compared to households with a history of domestic violence, but without the presence of a gun (Raissian, 2016).…”
Section: Firearms and Femicidementioning
confidence: 96%
“…One study of the effect of the Lautenberg Amendment on domestic homicides found a 17% reduction in female partner homicides and a 25% reduction in domestic child homicides (Raissian, 2016). Another study found that additional state level laws on misdemeanor domestic violence gun prohibition did not lead to any reduction in IPH beyond the effect of federal law, but that additional state level restraining order gun prohibitions reduced IPH by 8% (Vigdor and Mercy, 2006).…”
Section: Domestic Violence Restraining Orders and Firearmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that state‐level DVRO firearm restrictions are associated with reductions in intimate partner homicide (Vigdor & Mercy, ; Zeoli & Webster, ; Zeoli et al., ), particularly when these restrictions are extended to dating partners (who are not covered under the federal law or in some states), ex parte DVROs (which are temporary or emergency orders put in place before a full hearing and are also not covered under federal law), and when a state has legislated that a judge can or must order that prohibited DVRO respondents relinquish any firearms in their possession (Diez et al., ; Zeoli et al., ). Additionally, the federal MCDV firearm restriction has been associated with reductions in intimate partner homicides committed with firearms (Raissian, ; Zeoli et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The appellate process had the effect of creating a staggered implementation of the Lautenberg Amendment, providing a natural experiment for evaluating its effects. In a careful study, Raissian () found that implementation caused a substantial reduction in gun homicide against family members with no evidence of an increase in nongun homicide…”
Section: Major Research Findingsmentioning
confidence: 99%